2023
DOI: 10.3389/fmed.2022.1039232
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular catheter use in Latin America (the vascular study): A multinational cross-sectional study

Abstract: BackgroundPeripheral intravenous catheter (PIVC) insertion is one of the most common clinical procedures worldwide, yet little data are available from Latin America. Our aim was to describe processes and practices regarding PIVC use in hospitalized patients related to hospital guidelines, characteristics of PIVC inserters, prevalence of PIVC complications, and idle PIVCs.MethodsIn 2019 we conducted a multinational, cross-sectional study of adult and pediatric patients with a PIVC in hospitals from five Latin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Walker et al (19) objetivaron que en 9.620 CVP evaluados, el 59% del total de catéteres se instaló en servicios medico quirúrgicos, seguido de un 24% en salas de emergencia y 76% de éxito al primer intento en enfermeras, similar a nuestro estudio en donde el 60% correspondió a servicios medico quirúrgicos adultospediátricos, seguido de 20% en urgencias. La tasa de éxito al primer intento de los dispositivos con registro del número de intentos correspondió a 77,7% para el bloque adultos y 78,5% al bloque pediátrico, no obstante, el 69,7% de los CVP instalados no tenían registro del número de intentos, esta brecha puede tener relación al reciente enfoque implementado de evaluación de usuarios de difícil acceso venoso (DIVA), en donde el número de intentos para el éxito de la instalación del dispositivo toma absoluta relevancia al momento de elegir el tipo de catéter venoso periférico.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Walker et al (19) objetivaron que en 9.620 CVP evaluados, el 59% del total de catéteres se instaló en servicios medico quirúrgicos, seguido de un 24% en salas de emergencia y 76% de éxito al primer intento en enfermeras, similar a nuestro estudio en donde el 60% correspondió a servicios medico quirúrgicos adultospediátricos, seguido de 20% en urgencias. La tasa de éxito al primer intento de los dispositivos con registro del número de intentos correspondió a 77,7% para el bloque adultos y 78,5% al bloque pediátrico, no obstante, el 69,7% de los CVP instalados no tenían registro del número de intentos, esta brecha puede tener relación al reciente enfoque implementado de evaluación de usuarios de difícil acceso venoso (DIVA), en donde el número de intentos para el éxito de la instalación del dispositivo toma absoluta relevancia al momento de elegir el tipo de catéter venoso periférico.…”
Section: Discussionunclassified
“…Al igual que en el estudio realizado por Chen et al (7) las causas más frecuentes de fracaso estuvieron relacionado a flebitis, infiltración y extravasación. A nivel de Latinoamérica y de acuerdo con "The Vascular Study" publicado en 2023, se logró cuantificar que, del total de dispositivos, el 14% se encontraba con fijación no estaban limpios, secos e intactos, un 6% con sangre en el tubo o conexiones y 3% sangre seca alrededor del sitio del catéter (19). Por otra parte, un estudio observacional realizado en personas mayores hospitalizadas de medicina interna evidenció tasas de complicaciones asociadas a 21,5 x 1.000 días para retiro accidental, 16,2 x 1.000 días para infiltración /obstrucción y 15 x 1.000 días para flebitis (33).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Furthermore, a study that demonstrated the insertion and maintenance processes of peripheral intravenous catheters in 132 hospitals in five Latin American countries (Argentina, Brazil, Chile, Colombia and Mexico), covering 9620 peripheral intravenous catheters, identified results indicating the 3 de LETTER TO THE EDITOR need for advances in evidence-based clinical practice to promote better indicators, since there are more than 25% failure in the first puncture, 29% of the catheters are inserted in the veins of the hand, 19% stabilized with non-sterile tapes, 18% of the observed catheters had signs of adverse events, reaching a an average length of stay of one day (3) .…”
Section: Dear Dr Dulce Aparecida Barbosa Editor In Chief Of the Revis...mentioning
confidence: 99%
“…Still, one in every four patients is subjected to consecutive puncture attempts by clinicians, leading to vessel health harm and depletion over time, with significant impact on patients (e.g., pain, distrust, delays in treatment), healthcare professionals (e.g., anxiety, increased care volume and complexity) and health organizations (e.g., longer admission periods, increased care costs) (1)(2) . Thus, implementing formal assessment of venous assessment with standardized instruments will likely increase the identification of patients at higher risk of difficult intravenous access (DIVA) and the adoption of differentiated techniques (e.g., ultrasound-guided PIVC), leading to better patient outcomes and care experience (1,3) .…”
mentioning
confidence: 99%